A positive feedback circuit comprising p21 and HIF‐1α aggravates hypoxia‐induced radioresistance of glioblastoma by promoting Glut1/LDHA‐mediated glycolysis. Issue 3 (24th February 2022) - Jin, Xiaodong; Kuang, Yanbei; Li, Linying; Li, Hongbin; Zhao, Ting; He, Yufang; Di, Cuixia; Kang, Jian; Yuan, Lingyan; Yu, Boyi; Li, Qiang
Abstract: The radioresistance induced by hypoxia is the major obstacle in the successful treatment of cancer radiotherapy. p21 was initially identified as a widespread inhibitor of cyclin‐dependent kinases, through which mediates the p53‐dependent cell cycle G1 phase arrest in response to a variety of stress stimuli. In this study, we discovered a novel function of p21, which participated in the regulation of metabolic pathways under hypoxia. We found that p21 was upregulated in glioblastoma (GBM) cells under hypoxic conditions, which enhanced the radioresistance of GBM cells. In principle, HIF‐1α is bound directly to the hypoxia response elements (HREs) of the p21 promoter to enhance its transcription activity, in turn, p21 also promoted the transcription of HIF‐1α at the mRNA level and maintained HIF‐1α function under oxygen deficiency. The positive correlation between p21 and HIF‐1α augmented Glut1/LDHA‐mediated glycolysis and aggravated the radioresistance of GBM cells. Thus, our results constructed a positive feedback circuit comprising p21/HIF‐1α that might play a key role in enhancing the radioresistance of GBM under hypoxia.